Altura, disponibilidad de forraje y relación hoja-tallo del pasto estrella solo y asociado con leucaena - Maya German Eduardo (Acta Agronómica)
Los cortes se realizaron a los 28, 35 y 42 días en la hacienda Lucerna, norte del Valle del Cauca, Colombia (960 msnm, 24°C, 1100 mm anuales, 75% 80% de humedad relativa, 3.6 mm de evaporación promedia mínima diaria. El diseño experimental fue de parcelas divididas con cuatro repeticiones, con dos épocas secas y dos de lluvias. La altura en estrella asociada fue significativamente superior (P<0.05), con valores de 39.2, 61.4, y 68.2 cm a 28, 35 y 42 días. Los valores de materia seca/corte fueron significativos (P<0.05) a los 35 días en favor de estrella asociada. Estrella sola produjo más hojas. Leucaena obtuvo 133.3, 162.4 y 175.9 cm; 11.51, 13.07 y 10.54 para relación H/T; 0.37, 0.63 y 0.75 t/ha/corte; 4.77, 6.59 y 6.51 t/ha/año, a los 28, 35 y 42 días. El sistema estrella+leucaena fue superior con tendencia a los 35 días.

Palabras claves: sistema de cultivo, Cynodon nlemfuensis, Leucaena leucocephala, plantas forrajeras, disponibilidad de forraje, relación hoja/tallo, altura.

ABSTRACT

Plant height, forage production in dry matter and leaf/stem ratio evaluations of stargrass pure and in association with leucaen. Were evaluated at 28, 35 and 42 cutting days at â€œ Lucernaâ€? farm, north of Cauca Valley, Colombia, (960 m.o.s.l., 24°C, 1100 mm per year, 75-80% of relative humidity, average 3.6 mm of daily evaporation) The experimental design was parcels divided with four repetitions, with two dry times (supported by irrigation) and two of rains. The height in associate stargrass was biggest (P<0.05) respect of pure one, with values of 39.21; 61.4, and 68.2, cm to 28, 35 and 42 days. The values of dry matter were significant (P<0.05) at 35 days in favor of associate one. Leat/Stem relationship indicated that pure stargrass produced more leaves. Leucaen obtained 133.3, 162.4 and 175.9 cm for height; 11.51, 13.07 and 10.54 for L/S relation; 0.37, 0.63 and 0.75 t/ha/cutting; 4.77, 6.59 and 6.51 t/ha/year, at 28, 35 and 42 days. The stargrass+leucaen system went superior with tendency to the 35 days.

Key words: associated system, stargrass, Cynodon nlemfuensis, leucaen, Leucaena leucocephala, forages, availability of forage, leaf/stem relation, plant height.